Hydroporus kraatzii Schaum 1868 - Fery, Hans (Zenodo, 2009)
Hydroporus kraatzii Schaum, 1868 Hydroporus kraatzii Schaum, 1868 in KRAATZ (1868: 384) (original description). Hydroporus kraatzii Schaum, 1868 in SCHAUM & KIESENWETTER (1868: 66), syn. nov. (objective junior synonym and primary homonym, preoccupied by H. kraatzii Schaum, 1868 in KRAATZ (1868: 384); synonymy personally communicated by A. N. Nilsson, Umeå, Sweden). Hydroporus kraatzii Schaum, 1868 in SCHAUM & KIESENWETTER (1868: 66): SHARP (1882: 481) – NILSSON & HOLMEN (1995: 67) – NILSSON (2009a: 146). Hydroporus kraatzi Kiesenwetter, 1868: GEMMINGER & HAROLD (1868: 435) (incorrect authorship, referring to H. kraatzii Schaum, 1868 in SCHAUM & KIESENWETTER (1868)). Hydroporus kraatzi Schaum, 1868: ZIMMERMANN (1919: 169, 1920: 88, 1931: 153). – SCHAEFLEIN (1971: 38). Hydroporus hedwigi Reitter, 1897: 45: ZIMMERMANN (1919: 169) (synonymy with H. kraatzii ). – NILSSON (2007: 51). Hydroporus hedwigae Schenkling, 1917: 52 (unjustified emendation of H. hedwigi Reitter): NILSSON (2007: 51) (synonymy). Type locality. Poland, ‘ Glatzer Schneeberg’ [‘Schneeberg’ = ‘snow mountain’; this mountain is called Králický Sněžník in Czech and Śnieżnik Kłodzki in Polish]. The border between the Czech Republic and Poland runs exactly across the peak of the mountain. The co-ordinates of the ‘ Glatzer Schneeberg’ are given in Wikipedia (access January 2009) as 50.201N 16.849E. According to KRAATZ (1968: 384), Kraatz himself collected at least some specimens on the northern slope of the ‘Glatzer Schneeberg’. It is therefore more likely that the type locality is in Poland and not in the Czech Republic. Type material. LECTOTYPE (by present designation): J, a small rectangular dark blue label, ‘Type’ [hw Cl. Müller], ‘Glatzer Schneebg’ [hw Cl. Müller], ‘Type von Hydr. Kraatzi Schaum’ [red, hw?], ‘ Lectotype, Hydroporus kraatzii Schaum, 1868, des. H. Fery 2009 ’ [red, printed] (ZSM). Notes on the type material. According to HORN et al. (1990: 345) and SCHERER (1982: 60), at least parts of Schaum’s Hydroporinae came ‘via E. A. H. v. Kiesenwetter, via Cl. Müller’ to the ZSM in 1905. It is known from other Schaum’s types that at least some of them were provided with a small rectangular dark blue label and/or that Clemens Müller, owing to his knowledge about the origin of the specimens, added labels in his own handwriting (see FERY 1992a: 67, 1992b: 119, 1992c: 343, 351; FERY et al. 1996: 315; FERY & BRANCUCCI 1997: 247). Thus, I have no doubt that the designated lectotype is a (former) syntype of H. kraatzii Schaum, 1868. HORION (1941: 393) reported that ‘types’ should be stored in the Deutsches Entomologisches Institut (DEI). However, DÖBLER (1976) did not list any types of H. kraatzii in the collections of the DEI and I have not been able to find such specimens during several visits at that institute. The first publication of the name Hydroporus kraatzii (KRAATZ 1868: 384) cites the species as ‘ Hydroporus Kraatzii Schaum n. sp. in litt.’ Although the author of that work is Kraatz, the authorship of the taxon must be assigned to Schaum because he is cited as the author. In addition, the taxon was described by Schaum a second time in SCHAUM & KIESENWETTER (1868: 66) (compare Article 50.1.1 including the Example in ICZN 1999). : Published as part of Fery, Hans, 2009, New species of the Hydroporus longulus-group from Iran, Armenia and Turkey with a synopsis of the group (Coleoptera: Dytiscidae), pp. 529-558 in Acta Entomologica Musei Nationalis Pragae 49 (2) on pages 550-551, DOI: 10.5281/zenodo.5320178 : {"references": ["KRAATZ G. 1868: Beitrage zur Kenntnis der deutschen Kaferfauna. Zweites Stuck. Berliner Entomologische Zeitschrift 11 (1867): 384 - 388 [published in January 1868].", "SHARP D. 1882: On aquatic carnivorous Coleoptera or Dytiscidae. Scientific Transactions of the Royal Dublin Society, Series 2 2: 179 - 1003 + pls. 7 - 18.", "NILSSON A. N. & HOLMEN M. 1995: The aquatic Adephaga (Coleoptera) of Fennoscandia and Denmark, II. Dytiscidae. Fauna Entomologica Scandinavica 32: 1 - 192.", "NILSSON A. N. 2009 a: A World Catalogue of the family Dytiscidae, or the diving beetles (Coleoptera, Adephaga). BETA-version dated 29.12. 2008, privately distributed in pdf format in January 2009.", "GEMMINGER M. & HAROLD E. DE 1868: Catalogus Coleopterorum hucusque descriptorum synonymicus et systematicus. Tom II. E. H. Gummi, Monachii, pp. 425 - 752.", "ZIMMERMANN A. 1919: Die Schwimmkafer des Deutschen Entomologischen Museums in Berlin-Dahlem. Archiv fur Naturgeschichte 83 A (12) (1917): 68 - 249.", "ZIMMERMANN A. 1920: Dytiscidae, Haliplidae, Hygrobiidae, Amphizoidae. In: SCHENKLING S. (ed.): Coleopterorum Catalogus, Vol. 4, pars 71. W. Junk, Berlin, 326 pp.", "ZIMMERMANN A. 1931: Monographie der palaarktischen Dytiscidae, II. Hydroporinae (2. Teil: Die Gattung Hydroporus Clairv.). Koleopterologische Rundschau 17: 97 - 159.", "REITTER E. 1897: Neunter Beitrag zur Coleopteren-Fauna von Europa und den angrenzendern Landern. Wiener Entomologische Zeitung 16: 45 - 47.", "NILSSON A. N. 2007: Some necessary corrections of the spelling of species-group names within the family Dytiscidae (Coleoptera). Zootaxa 1615: 49 - 54.", "SCHENKLING S. 1917: Erklarung der wissenschaftlichen Kafernamen aus Reitter's Fauna Germanica. Schriften des Deutschen Lehrervereins fur Naturkunde 34: 1 - 80.", "FERY H. & ERMAN O. K. 2009: Five new species of the longulus-group of Hydroporus Clairville, 1806 from north-eastern Turkey (Coleoptera: Dytiscidae). Zootaxa 2033: 1 - 12.", "HORN W., KAHLE I., FRIESE G. & GAEDIKE R. 1990: Collectiones entomologicae, ein Kompendium uber den Verbleib entomologischer Sammlungen der Welt bis 1960. Teil II: L - Z. Akademie der Landwirtschaftswissenschaften der DDR, Berlin, pp. 223 - 573.", "SCHERER G. 1982: Chronik der Sektion Coleoptera der Zoologischen Staatssammlung Munchen. Spixiana, Supplement 7: 57 - 65.", "FERY H. 1992 a: Revision der \" minutissimus-Gruppe \" der Gattung Bidessus Sharp (Coleoptera: Dytiscidae). Entomologica Basiliensia 14 (1991): 57 - 91.", "FERY H. 1992 b: Coelambus lagari n. sp. und Coelambus sanfilippoi n. sp. aus dem westlichen Mittelmeergebiet (Coleoptera: Dytiscidae). Entomologische Zeitschrift 102 (7): 113 - 124.", "FERY H. 1992 c: Revision der saginatus-Gruppe der Gattung Coelambus Thomson (Coleoptera: Dytiscidae). Linzer Biologische Beitrage 24 (1): 339 - 358.", "FERY H., FRESNEDA J. & MILLAN A. 1996: Bemerkungen zur Nebrioporus ceresyi-Gruppe sowie Beschreibung von Nebrioporus schoedli n. sp. (Coleoptera: Dytiscidae). Entomologische Zeitschrift 106 (8): 306 - 328.", "FERY H. & BRANCUCCI M. 1997: A taxonomic revision of Deronectes Sharp, 1882 (Insecta: Coleoptera: Dytiscidae) (part I). Annalen des Naturhistorischen Museums in Wien 99 B: 217 - 302.", "HORION A. 1941: Faunistik der deutschen Kafer, I. Adephaga - Caraboidea. Goecke Verlag, Krefeld, 463 pp.", "DOBLER H. 1976: Katalog der in den Sammlungen des ehemaligen Deutschen Entomologischen Institutes aufbewahrten Typen - XIV. (Coleoptera: Dytiscidae, Haliplidae, Gyrinidae, Rhysodidae, Paussidae). Beitrage zur Entomologie 26 (1): 179 - 186.", "ICZN 1999: International code of zoological nomenclature. Fourth edition. The International Trust for Zoological Nomenclature, London, 306 pp."]}